On Calling People ‘Prophets’ in 1970 - Towner, W. Sibley (Interpretation, 1970)
The investigation of the modern use of a term such as ‘prophet’ is more than simply an exercise in language analysis; for Jew and Christian, it forms part of the larger quest for the locus of authoritative moral and religious utterance in our time.